THE INFLUENCE OF WORD OF MOUTH, PRODUCT QUALITY AND SALES PROMOTION ON PURCHASING DECISIONS FOR SHINZUI BRAND BATH SOAP PRODUCTS BY THE PUBLIC IN LANGSA CITY - Anggita Prinanda; Rusydi Abubakar; Sapna Biby; T. Edyansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The purpose of this study was to determine the effect of Word of Mouth, Product Quality and Sales Promotion on Purchasing Decisions for Shinzui Brand Bath Soap Products by the Public in Langsa City. Data for this study were collected through a survey method using a questionnaire as a data collection instrument. The population in the study were 119 consumers who used shinzui brand bath soap products in Langsa city. This study uses a quantitative approach with linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. Hypotheses, coefficients are determined using the SPSS version 25.0 programme. The results of this study indicate that partially sales promotion has no positive and significant effect on purchasing decisions on shinzui brand bath soap products by people in the city of Langsa, while word of mouth, and product quality have a positive or significant effect on purchasing decisions for shinzui brand bath soap products by people in the city of Langsa. Simultaneously, each variable word of mouth, product quality and sales promotion has a positive and significant effect on purchasing decisions for shinzui brand bath soap products by the public in the city of Langsa. The R Square value of 0.159 obtained from the variables can be explained by the independent variables, namely word of mouth, product quality and sales promotion 15.9% while the remaining 84.1% can be explained by other variables not analysed by this study.